Pengaruh penambahan ekstrak kental daun kelapa sawit (Elaeis Guineensis Jacq.) terhadap viskositas krim tabir surya antijerawat - Dominica, Dwi; Putri , Yona Harianti; Versita , Riana; Shufyani , Fahma (Journal of Pharmaceutical and Sciences, 2025)
Introduction: ROS due to sun exposure can damage the skin. Skin structures that are damaged or thinned cause the risk of acne on the skin, one of which is that the skin can be infected with acne-causing bacteria. Palm leaf (Elaeis guineensis Jacq.) is one of the plants that has good antioxidants and antibacterial. The aim: This study aims to determine the effect of the addition of extracts on the viscosity of anti-acne sunscreen creams. Methods: This study was experimental by conducting a viscosity test of sunscreen preparations using a brokfield viscometer. The results of this study show that Formula F1 (1.5%) has the highest viscosity of 8,970 cPs, followed by F2 (3%) at 7890 cPs, and F3 (4.5%) at 7090 cPs which is included in the good viscosity range. Sunscreen creams have pseudoplastic flow properties. Conclusion: the higher the concentration of the extract, the greater the viscosity of the preparation.